Eosinophilic Cholangitis and Wirsungitis as Cause of Simultaneous Bile Duct Obstruction and Pancreatitis - Kroemer, A.; Sabet-Baktach, M.; Doenecke, A.; Ruemmele, P.; Scherer, M. N.; Schlitt, H. J.; Breidert, M. (Zeitschrift für Gastroenterologie, 2012)
Eosinophilic cholangitis is a rare clinical entity characterised by transmural eosinophilic infiltration of the biliary system. The aetiology of this disease is still unclear. We report on a 49-year-old male patient who presented with symptoms of obstructive jaundice and imaging suggestive for periampullary carcinoma. After partial pancreatoduodenectomy for suspected pancreatic cancer, pathology revealed massive eosinophilic cholecystitis as well as intra- and extrahepatic eosinophilic cholangitis with pseudopolypoid papillary lesions. Our case illustrates the diagnostic pitfalls in eosinophilic cholangitis as careful imaging procedures − optimally interdisciplinary − should be considered and performed in such patients. In conclusion, eosinophilic cholangitis is an uncommon, inflammatory condition that needs to be considered as a differential diagnosis for periampullary malignancies.
Keywords: biliary obstruction; eosinophilic cholangitis; pancreatitis; pancreatic cancer